hello
since this requires an explicit equation we need to define some terms first
a = -2
common difference = -4
![F(n)=a+(n-1)d](https://img.qammunity.org/2023/formulas/mathematics/college/cc4m37ierqqefn6afxd8b0gb6h4were4mh.png)
all we need to do is substitute the values of a and d into the equation above
![\begin{gathered} f(n)=a+(n-1)d \\ f(n)=-2+(n-1)\cdot-4 \\ f(n)=-2-4n+4 \\ f(n)=2-4n \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dswili0fpv39q2v7wfuzammfx1fcukz8ad.png)
the explicit equation for this series is 2 - 4n
test for f(3) and f(4)
![\begin{gathered} f(3)=2-4(3) \\ f(3)=2-12 \\ f(3)=10 \\ \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/124zp4zapv9dta164v5nvhe8fwpf1izwec.png)
![\begin{gathered} f(4)=2-4(4) \\ f(4)=2-16 \\ f(4)=-14 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fmbsftagqc2v5gzlj515g166yf35plhntn.png)